Risk factors and markers of inflammation of comorbid allergic diseases: rhinitis and bronchial asthma - R. Z. Tikhonova; R. M. Fayzullina (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Introduction. Today there has been a steady increase in the allergic pathology of the respiratory tract - bronchial asthma and allergic rhinitis in pediatric practice. Despite the use of modern diagnostic approaches, we cannot say with certainty which combined effect of which factors leads to the development of allergic inflammation of the respiratory tract. The study of risk factors for the formation of allergic rhinitis and asthma in children is necessary for timely early diagnosis with the subsequent development of an individual strategy for preventive measures.Objective: to study risk factors and markers of allergic inflammation in children with allergic rhinitis, rhinitis and bronchial asthma and only with bronchial asthma.Materials and methods. The study involved 107 children suffering from allergic rhinitis, allergic rhinitis and bronchial asthma, and only bronchial asthma. All patients underwent clinical, laboratory, functional, allergological examination, analysis of the cellular composition of bronchial and nasal secretions.Results. The analysis revealed factors influencing the development of bronchial asthma, allergic rhinitis and comorbid diseases, as well as markers of allergic inflammation. There were trends in detecting a higher level of eosinophils in blood, nasal and bronchial secretions in a group of children with a comorbid condition - bronchial asthma and allergic rhinitis.Conclusion. Evaluation of the level of markers of allergic inflammation of nasal and bronchial secretions can be used as additional criteria for early diagnosis, prediction of the severity of bronchial asthma and allergic rhinitis in children, serve as a monitoring method, development of personalized preventive measures for this group of children.